Geographical Diversification Effects on Banks’ Performance: Evidence from Islamic Banks of some Selected Countries - Faten Zoghlami (STIE Malangkucecwara, 2020)
This paper investigates the impact of geographic diversification onthe performance of Islamic banks. Using an unbalanced panel dataset of 54 Islamic banksimplemented in the GCC and Southeast Asia regions, during the 2004-2016 period,the core question is to analyze the effect of both diversification intra and beyond homecountries on Islamic banks credit risk, stability, and profitability. This research assertsthat geographical diversification within the home country seems to enhance Islamic bankstability, profitability but does not improve loan quality. More pronounced results arereported when banks expand intra and beyond the home country frontier. These findingsare consistent with the view that geographic expansion helps to strengthen stabilitythrough diversification of the specific region risk, but the related loan growth makes itmore difficult to assess and monitor credit risk. These findings have strategic implicationsfor bank managers, regulators, and supervisors about the consequences of Islamic bankgeographic expansion.